Management of Primary Spontaneous Pneumothorax in a Third-Level Pediatric Surgical Center: A Retrospective Study - Spezzotto, Giovanna; Boscarelli, Alessandro; Giangreco, Manuela; Ceschiutti, Giulia; Codrich, Daniela; Scarpa, Maria-Grazia; Iaquinto, Marianna; Olenik, Damiana; Guida, Edoardo; Schleef, Jürgen (Frontiers in Pediatrics, 2022)
INTRODUCTION: The management of primary spontaneous pneumothorax (PSP) in pediatrics remains controversial. The aim of this study was to investigate the risk of recurrence after non-surgical treatment versus surgery, the difference in the length of stay (LOS) between various treatment options, and the role of computed tomography (CT) in the management of PSP. MATERIALS AND METHODS: We retrospectively reviewed patients admitted to our Pediatric Surgery Unit for an episode of PSP between June 2009 and July 2020. Medical records including clinical presentation at admission, diagnostics, treatments, complications, and LOS were collected. RESULTS: Twenty-three patients (22 males and 1 female) were included in this study. Median age was 15.65 (range 9-18). Chest X-rays were performed in all patients and showed 5 small (22%) and 18 large (78%) PSP. Chest drain was used for large PSP (≥2 cm) if the patient was clinically unstable. Eleven patients (48%) were managed non-operatively with observation alone and a recurrence rate of 18%, chest drain was used in 11 patients with a recurrence rate of 36%, and surgery was deemed necessary as a first treatment choice in one case. Six patients (27%) had an episode of relapse after non-operative management or chest drain placement. Following surgery, a relapse occurred in 2 of the 6 patients. Chest drain insertion was associated with a longer LOS than observation alone (6.36 vs. 2.4 days), and surgery resulted in a longer LOS than other types of treatment (P = .001). CONCLUSION: According to our experience, small PSP or clinically stable larger PSP can be treated conservatively with observation alone. Operative management should be taken into consideration in children with large symptomatic PSP, persistent air leak, and/or relapse after chest drain insertion.